The Relationship Between Flexible Work Arrangements and Employee Engagement Among Managerial Employees in the Private Sector - Surena, Sabil; Zaiton, Hassan; Shu Yun, Lim (UNIMAS Publisher, 2024)
Today, it is common practice for most organisations to implement flexible work arrangements in order to meet the needs of their employees and ensure the long-term viability of the business. It got its beginnings during the COVID-19 pandemic, and as the techniques have spread, they have unquestionably changed many facets of peoples' lives and forced societies, corporations, nations, and individuals to reconsider how they live and work. Flexible work arrangements have become the new norm as a result of the epidemic forcing more workers to work remotely or with less hours in the workplace. Therefore, the purpose of this study is to identify the relationship between flexible work arrangements, such as flexible time, telecommuting, and flexible leave towards employee engagement among managerial employees in one of the private sectors in Selangor. Employing a quantitative approach through a correlational study has been adopted to test the hypotheses to this relationship. The population of this study comprises 52 managerial employees from middle and first-line manager. A convenience sampling method was employed for data collection through the distribution of questionnaires via Google Form Link. The results of this research, using Spearman correlation analysis, indicate a significant relationship between flexible work arrangements, specifically flexible time and telecommuting, and employee engagement. Therefore, it is recommended that organizations review their existing policies and practices to better accommodate the current situation and the needs of their employees.